以關注本位採用模式詮釋教師實施海洋教育之個案研究 Using Concerns-Based Adoption Model (CBAM) to Interpret How Teachers Implement Marine Education: A Case Study - 李弘善 Hung-Shan Li; 劉湘瑤 Shiang-Yao Liu (National Changhua University of Education, 2019)
海洋教育是融入基本教育課程的重大議題之一，屬於跨領域的題材，教師必須有相當程度的專業能力方能勝任。從文獻回顧得知教師實施海洋教育遇到的困難，因此本研究引用「關注本位採用模式」（Concerns-Based Adoption Model, CBAM）的架構，並依照個別教師的需求提供客製化的海洋主題教學諮詢。研究者透過舉辦研習以及網路等方式，公開招募志願參與的教師組成社群並接受諮詢介入。研究者藉由CBAM 的三項研究工具，以個案分析的方式，詮釋教師在介入後實施海洋教育的方式：「關注階層」（Stages of Concern, SoC）用以評估教師實施海洋教育過程中情意層面的變化；「使用階層」（Levels of Use, LoU）分析教學行動的改變；「創新配置」（Innovation Configurations,IC），則呈現課程實施的方式與內容。研究者亦收集現場課室觀察與訪談、網路聊天室等質性資料，交叉檢核前述工具分析的結果。共計17 名教師參與本研究，任教階段從幼教到高中職皆有，資歷和專業需求各有不同。本研究的結論為：教師接受介入後，可以解決部分實施海洋教育的困難；關注階層不一定全面提升，但是呈現多元樣貌。使用階層則普遍提升，其中六位教師甚至達到最高等級；創新配置的分析則顯現海洋教育的方式與內容豐富多樣。本研究也發現：教師教學的改變是「需要溝通協調的歷程」，必須考慮個別教師的需求而提供合適的專業成長方案。 Marine education has been a crucial agenda addressed in both elementary and secondary school curricula. Due to the interdisciplinary nature of marine education, most teachers lack related subject matter knowledge and are unfamiliar with the pedagogies. Various literature reviews have revealed obstacles hindering teachers from carrying out marine education, and therefore a professional development program was designed in this study to meet teachers' demands. The program was based on the framework of the Concerns-Based Adoption Model (CBAM), which not only can be used to probe educational innovations, but also provides customized consultation in response to individual requirement. Three tools were used to interpret the effects of intervention: Stages of Concern (SoC) questionnaire reveals the affective changes; Levels of Use (LoU) interviews record the behavioral changes; and Innovation Configurations Map (IC Map) demonstrates the content of teaching. Professional development workshops and on-line platforms were held to recruit long-term participants from different levels of schools who cooperated with the research team. Presentations to participants' classrooms were carried out, and hands-on activities as well as equipment were designed or provided according to individual requirements. Thus, customized needs were satisfied through lengthy discussions between participants. Apart from the data, classroom observations, interviews, and on-line discussions were collected to ensure the validity of the study. For the behavioral aspects, the results show that all participants' LoU advanced to higher levels; their LoU reached IVA and above, and six of them even hit the highest level, indicating all of them can carry out marine education routinely. For the perceptions about marine education, however, not all participants' SoC manage to enter into higher stages. Moreover, IC indicates the diversified modes of marine education observed from individual teachers. Based on these findings, the researchers argue that change of teaching is "a process resulting from communication and coordination," indicating that stakeholders must seriously take individuals' needs into account and provide customized professional development projects for teachers.